Clinico-Pathological Study of Ocular Surface Squamous Neoplasia in a Tertiary Care Centre of Western Region of Nepal - Patel, Sushila; Pokharel, Binita Bhattarai; Shah, Anita; Goda, Manita Sunam; Thapa, Saraswati Khadka (Journal of Universal College of Medical Sciences, 2019)
INTRODUCTION: Ocular surface squamous neoplasia (OSSN) consists of a wide range of conjunctival and corneal lesions ranging from dysplastic lesions to invasive squamous cell carcinoma. In recent times, the incidence of OSSN seems to be on the rise, especially in developing countries. The present study was aimed to analyse demographic pattern, clinical characteristics, and histopathology findings of OSSN in a tertiary care centre of western region of Nepal. MATERIAL AND METHODS: It was a retrospective study. We analyzed 94 cases of OSSN who presented to cornea department of Lumbini Eye Institute, Bhairahawa, Nepal over a period 1.5 years from 1st July 2017 to 31st December 2018. All the patients with OSSN, detailed clinical history and examination were recorded. Lesions were excised with a 3 mm margin clearance and sent for histopathological examination. RESULTS: Mean age of our patients with OSSN was 48.89±17.955 years ranging from 17 to 85 years. There were 52 (55.32%) male and 42 (44.68%) female. Mean duration of presentation was 6.34±6.17 months. A solitary nodule at the limbus was the commonest presentation. Right eyes were involved more than left eyes. Lesions were found most commonly on temporal site 52 (55.32%) followed by nasal 36 (38.30%). On histopathological examination benign lesions were found in 31 (32.98%) eyes, preinvasive lesion in 50 (53.19%) eyes and invasive lesions in 13 (13.83%) eyes. CONCLUSION: OSSN were seen more commonly in young adults with male predominance. Benign and pre invasive lesions are found more commonly than invasive lesions.